Chapter Lyonnais silks «ad uttimo gusto»: the trade in fashionable waistcoats between France and Italy in the second half of the 18th century - Dato, Moïra (Datini Studies in Economic History, 2022)
Throughout the 18th century, Lyonnais silk manufacturing was constantly creating, adapting and transforming products in response to the evolution of fashion, which was both a profitable tool and a turbulent stream to harness. The male waistcoat is an excellent example of the difficult exercise in which merchant manufacturers engaged in order to secure their markets. Although not originally a specialty of the French city, the waistcoat eventually became a key item in Lyonnais production, selling very successfully in France and abroad. In this article, we analyse trade with Italy in order to explore in detail how the Lyonnais adapted to changes in fashion and used them to their advantage in order to stimulate consumption while navigating the challenges of a foreign market.